دراسة مقارنة لتقييم فعالية التتراكوساكتيد (سيناكتين) واستخدام المفجر على الاختلاطات التالية للقلع الجراحي للأرحاء الثالثة السفلية المنطمرة - أسعد, منذر; خليل, علي; عبد الوهاب, هلا (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في قسم جراحة الفم والفكين في كلية طب الأسنان بجامعة تشرين وشملت 40 حالة قلع جراحي لأرحاء ثالثة سفلية منطمرة ثنائية الجانب عند 20 مريضاً (أي إن كل مريض كان لديه اثنتان من الأرحاء الثالثة السفلية المنطمرة ) . توزعت عينة المرضى على مجموعتين: المجموعة الأولى: شملت 20 رحى عند 10 مرضى. تم إعطاء دواء تتراكوساكتيد ( سيناكتين ) قبل 24 ساعة من قلع الرحى الواقعة في إحدى الجهتين وبعد 24 ساعة من القلع مع صاد حيوي (augmentine) ومضمضة (chlorhexidine 0.12%) أما في الجهة الأخرى فتم وصف مضاد التهاب لا ستيروئيدي (ibuprofen) مع صاد حيوي (augmentine) ومضمضة (chlorhexidine 0.12%). المجموعة الثانية: شملت 20 رحى عند 10 مرضى. تم تطبيق مفجر (منزح) بشكل متزامن مع الخياطة مع وصف صاد حيوي (augmentine) ومضمضة (chlorhexidine 0.12%) في إحدى الجهتين أما في الجهة الأخرى فتم إجراء الخياطة بطريقة كلاسيكية مع وصف مضاد التهاب لا ستيروئيدي (ibuprofen) مع صاد حيوي (augmentine) ومضمضة (chlorhexidine 0.12%). تم تقييم متغيرات الألم والوذمة والضزز وطبيعة الحياة في جميع حالات القلع السابقة وذلك في الفترات الزمنية 24 ساعة، 72 ساعة، 7 أيام بعد القلع. أظهرت النتائج أن إعطاء دواء تتراكوساكتيد (سيناكتين) كان له تأثير إيجابي واضح على الوذمة والضزز في اليوم الأول و الثالث بعد القلع و طبيعة الحياة خلال الفترة التالية للقلع و لم يكن له تأثير على الألم،أما تطبيق المفجر فلم يكن له تأثير على المتغيرات السابقة. The study is performed in the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, University of Tishreen. It included 20 patients with bilateral impacted lower third molars (40 impacted lower third molars). Patients have been divided into two groups: First Group: It includes 10 patients with bilateral impacted lower third molars (20 molars). Every patient is given tetracosactide (synacthen) at 24 hours before extraction of one of the two molars and after 24 hours with an antibiotic (augmentine) and a mouthrinse (chlorhexidine 0.12%). But after extraction of the other molar, we have given the patient a nonsteroidal anti-inflammatory drug (ibuprofen) with an antibiotic (augmentine) and a mouthrinse (chlorhexidine 0.12%). Second Group: It includes 10 patients with bilateral impacted lower third molars (20 molars). We have inserted a drain during suturing with an antibiotic (augmentine) and a mouthrinse (chlorhexidine 0.12%) after extraction of one of the two molars, but after extraction of the other molar we did not insert a drain with a nonsteroidal anti-inflammatory drug (ibuprofen) an antibiotic (augmentine) and a mouthrinse (chlorhexidine 0.12%). Variables of pain, swelling, trismus, and quality of life were evaluated at 24 hours, 72 hours, and 7 days after the extraction. The results showed that tetracosactide (synacthen) hada significant effect on swelling and trismus at 24 hours and 72 hours after the extraction. It also had a significant effect on quality of life after the extraction. But, it didn't have any effect on pain. The results also showed that using a drain didn’t have any effect on those variables.